Eight species of the genus Glenea Newman, 1842 from the Oriental Region, with description of three new species (Coleoptera: Cerambycidae: Lamiinae: Saperdini) - Lin, Meiying; Tavakilian, Gérard; Montreuil, Olivier; Yang, Xingke (Zootaxa, 2009)
Eight species of Glenea Newman, 1842 from the Oriental Region are studied, including description of three new species: G. paradiana Lin et Montreuil sp. nov. from Vietnam & Laos, G. nigrorubricollis Lin et Yang sp. nov. from Guangdong, China and G. subrubricollis Lin et Tavakilian sp. nov. from Vietnam. Glenea theresae Pic, 1943 is regarded as a junior synonym of G. diana Thomson, 1865, and G. (Mesoglenea) invitticollis Breuning, 1956 as a junior synonym of G. flavorubra Gressitt, 1940. Glenea rufipes Gressitt, 1939 is reinstated from synonym of G. subsimilis Gahan, 1897. Habitus and terminalia are presented as photographs.